Comparison of the Effect of Eight Week Training Program Schedule With Two Different Stretching Patterns Strengthening on Changes in the Status of Lower Cross Syndrome - Chiman Alyarnezhad; Ali Shams Majalan (Islamic Azad University, Hamedan Branch, 2021)
Objective: Different timing of performing stretching and strengthening exercises can have different effects on the condition of Lower Crossed Syndrome (LCS). This study aims to compare the effects of eight-week training using stretching and strengthening exercises intermittently and simultaneously on the status of LCS in female college students. Methods: In this quasi-experimental study, the study population consists of 300 female students of Guilan University aged 19-25 years. To assess LCS, the New York Posture Rating tool was used. 120 patients who had hyperlordosis were re-evaluated using flexible ruler for precise measurement of LCS. Finally, 45 students with a lumbar curvature angle of >45 degrees were selected and randomly divided into three groups of intermittent training (n=15), simultaneous training (n=15), and control (n=15). The training program consisted of corrective exercises for 8 weeks, 3 sessions per week, each for 60 minutes. One-way ANOVA was used for data analysis in SPSS v. 20 software Results: The difference between the intermittent training and control groups was significant (P=0.30), while no significant difference was observed between the simultaneous training and control groups (P=0.68). Conclusion: Performing stretching and strengthening exercises intermittently has a greater effect on reducing LCS than performing these exercises simultaneously.